ANALISA WAKTU TEMPUH KENDARAAN BERMOTOR DENGAN METODE ESTIMASI INSTANTAEOUS MODEL DAN METODE KENDARAAN BERGERAK PADA JLN.YOS SUDARSO II – JLN.YOS SUDARSO III SANGATTA UTARA KABUPATEN KUTAI TIMUR - PABIANAN, HISAR FREDRIK (KURVA S JURNAL MAHASISWA, 2020)
Travel time is defined as the time needed to cover a certain distance and will determine a distance. And the research location of the travel time is loacated on the yos.sudarso II street – the yos.sudarso III street is sangatta utara kabupaten kutai timur. Using the Instantaeous Model method and Moving Observer Car method The results of the Instantaeous Model method analysis result get an average travel time yield (UTMS) of 7,889 minutes and an average travel time space (USMS) of 8,117 minutes The results of the the Moving Observer Car method analysis result get the largest average travel time of 7,946 minutes